Microstructure and Phase Composition of Thin Protective Layers of Titanium Aluminides Prepared by Self-propagating High-temperature Synthesis (SHS) for Ti-6Al-4V Alloy - Teichmanova, Anna; Michalcova, Alena; Necas, David (Manufacturing Technology Journal, 2022)
Titanium aluminides were prepared using self-propagating high-temperature synthesis (SHS) from powder aluminium and compact Ti-6Al-4V alloy at 800 °C. The resulting material was subsequently annealed at the same temperature for 3 hours. The coating was successfully bonded to the matrix using SHS while forming intermetallic phases of cubic TiAl3 in areas of powdered aluminium. The resulting coating was approximately 14 μm thick. Material annealing resulted in further reactions between the TiAl3 coating and Ti-6Al-4V matrix, forming a thin layer of γ-TiAl. Using SEM, the different phase composition of annealed and unannealed material was clearly visible, however, clear determination of emerging phases was very difficult due to the small thickness of the intermetallic coating. Eventually, phases were determined by a combination of cross-section μ-XRD and various EDS analyses.
Keywords: Self-propagating high-temperature synthesis (SHS); Titanium aluminides; Intermetallics; Coatings